Public Investment and Public-Private Partnerships - Akitoby, Bernardin (Economic Issues; Economic Issues ;, 2007)
Over the past three decades, public spending on infrastructure, as a share of GDP, has been on the decline worldwide. Although the link between infrastructure investment and economic growth is not yet fully understood, the quality of infrastructure clearly affects a country's productivity, competitiveness in export markets, and ability to attract foreign investment. This EI explores the following questions: Should countries increase public investment in infrastructure? If the answer is yes, how can they do so in a fiscally responsible manner? Are public-private partnerships a viable alternative?